2005
DOI: 10.3390/10111377
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Potent Antimicrobial Activity of Some Novel N-(Alkyl)-2-Phenyl-1H-Benzimidazole-5-Carboxamidines

Abstract: A series of 22 novel 1,2-disubstituted-1H-benzimidazole-N-alkylated-5-carboxamidine derivatives were synthesized and evaluated for in vitro antibacterial activity against S. aureus and methicillin resistant S. aureus (MRSA), E. coli, E. faecalis and for antifungal activity against C. albicans. Compound 59 [1-(2,4-dichlorobenzyl)-N-(2-diethylaminoethyl)-1H-benzimidazole-5-carboxamidine], with a 3,4-dichlorophenyl group at the C-2 position, displayed the greatest activity (MIC = 3.12 μg/mL against both some bact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 4 publications
0
20
0
Order By: Relevance
“…The concentration was adjusted to 100 lg/mL by four-fold dilution with culture media and bacteria solution. [10] of the high DMSO concentration (12.5%). Since compounds 54 and 58 are not soluble enough in DMSO/H 2 O (50%), their antimicrobial activity have not been determined by the tube dilution method; these compounds had some growth inhibition zone in the diffusion method.…”
Section: Resultsmentioning
confidence: 99%
“…The concentration was adjusted to 100 lg/mL by four-fold dilution with culture media and bacteria solution. [10] of the high DMSO concentration (12.5%). Since compounds 54 and 58 are not soluble enough in DMSO/H 2 O (50%), their antimicrobial activity have not been determined by the tube dilution method; these compounds had some growth inhibition zone in the diffusion method.…”
Section: Resultsmentioning
confidence: 99%
“…Benzimidazole ring is an important heterocyclic pharmacophore in drug discovery and the compounds carrying different substituents on benzimidazole structure are associated with a wide range of biological activities, including antibacterial properties [18,20,22,33]. A number of dicationically substituted bis-benzimidazoles originally developed as DNA binding agents have shown antibacterial activity [19,25,34,35].…”
Section: Introductionmentioning
confidence: 99%
“…The final products 5,6-dichloro-1H-benzimidazole-2-carboxamides (3)(4)(5)(6)(7)(8)(9)(10)(11)(13)(14) were prepared by the amidification of compounds 2 with appropriate amines by using O-(benzotriazol-1-yl)-N,N,N 0 ,N 0 -tetramethyluronium hexafluorophosphate (HBTU). Compound 12 was prepared by the reaction of compound 6 with methanolic HCl (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
“…It is also well known that amides, amidines, and combinations of both are present in a variety of antimicrobial, antiparasitic, anthelmintic, antiviral, and antitumoral agents. Furthermore, our previous work and that of others showed that benzimidazole carboxamidines display good antibacterial and antimycotic activity [2][3][4]. In addition, potent antimicrobial activities of a series of 5,6-dichloro-2-piperidin-4-yl-benzimidazoles [5] and 4-(5,6-dichloro-1H-benzimidazol-2-yl)-N-substituted benzamides [6] were reported.…”
Section: Introductionmentioning
confidence: 99%